JURIDICAL REVIEW OF DEFECTS MADE BY PT. PERHUTANI (PERSERO) IN THE PURCHASE OF THE BUILDING OWNED BY PT. VISI INVESTAMA PROPERTI (CASE STUDY OF SOUTH JAKARTA DISTRICT COURT DECISION NUMBER 735/PDT.GL202LLPN.JKT.SEL. JO JAKARTA HIGH COURT DECISION NUMBER26 - Pratama, Febrian; Napitupulu, Diana Ria W; Nadapdap, Binoto (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Basically, an agreement will go well if the parties to the agreement are based on good faith, but if one party does not have good faith or does not carry out their obligations, a breach of contract will arise. A breach of contract is a condition where the debtor does not fulfill his/her performance obligations in the agreement or does not fulfill them as they should or as they should In carrying out its business activities, a Limited Liability Company cannot be separated from agreement matters, one of which is PT. Visi Investama Properti, that PT. Visi Investama Properti as the owner of the Zuria Tower Building has an agreement to sell the Building to PT. Perhutani (Persero) then the agreement is stated in a deed of agreement. The main issue of the case is regarding the breach of promise (breach of contract) committed by PT. Perhutani (Persero) in carrying out the fulfillment of legal obligations in connection with the payment of the purchase of the Zuria Tower Building which has not been paid as stated in the Decision of the South Jakarta District Court Decision Number 735/PDT.GL202LLPN.JKT.SEL. Jo Jakarta High Court Decision Number 266/PDT/2023/PT DKI Jo. Supreme Court Cassation Decision Number 1755 K/PDT/2024. The method used in this study is normative research conducted as an effort to obtain the necessary data in connection with the problem. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. In addition, primary data is also used as supporting secondary data legal materials. For data analysis, it is carried out using qualitative legal analysis methods. From the research results, it can be obtained results based on the consideration of the panel of judges PT Perhutani (Persero) Proven to have been negligent (breach of contract) to PT. Visi Investama Properti as stipulated in Article 3 of the deed of agreement No. 88 dated December 26, 2019 That the Legal Consequences for the Parties in the Court's Decision PT Perhutani (Persero) is obliged to pay the remaining fine for late payment of the purchase of the Zuria Tower Building amounting to Rp. 8,232,300,000, - (eight billion two hundred thirty-two million three hundred thousand rupiah)